STRUKTUR MODAL, GOOD CORPORATE GOVERNANCE DAN KUALITAS LABA - Nadirsyah Nadirsyah; Fadlan Nur Muharram (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2015)
AbstractThe objective of the study was to examine the effect of capital structure and good corporate governance (GCG) on the earnings quality. The GCG variable are proxied by audit committees, independent commissioners, managerial ownership, and institutional ownership. The earnings quality measured by using Capital Adequacy Ratio (CAR) indicator with Earning Response Coeficient (ERC). The data was collected from the financial statements of the manufacture companies that listed at Indonesia Stock Exchange in the period between 2009 and 2013. By using purposive sampling and balanced panel data, there are 22 companies were selected as the sample. Multiple linier regression model is used to test the hypothesis The results of this study are capital structure, independent commissioners, audit committees, managerial ownership, and institutional ownership affected on the earnings quality simultaneously. Capital structure partially affected on the earnings quality. The audit committees, independent commissioners, managerial ownership, and institutional ownership affected on the earnings quality partially have an effect on the earnings quality. Keywords: capital structure, good corporate governance, earnings quality, ERC